2007
DOI: 10.1002/sim.2856
|View full text |Cite
|
Sign up to set email alerts
|

Wilcoxon‐based group sequential designs for comparison of areas under two correlated ROC curves

Abstract: Clinical studies to evaluate the relative accuracies of two diagnostic modalities via their receiver operating characteristic (ROC) curves are currently conducted using fixed sample designs: cases are accrued until a predetermined sample size is achieved and, at that point, the areas under the ROC curves are computed and compared (Radiology 1982; 143:29-36; Radiology 1983; 148:839-843). In prospective ROC studies (Radiology 1990; 175:571-575), participants are recruited from a clinically defined cohort and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“… Training is stopped when the cumulative increment in A U C o b t a i n e d i n f i v e consecutive steps is less than 1%. This rather soft stopping criterion is used instead of well-established statistical methods (Zhou et al, 2008) to avoid selecting too few predictors, which reduces the possibility of associating an effective probability of AHE with each integer score.  A testing dataset of the same size as the training set is used to evaluate model generalisation and to guide conclusive selection of the optimal predictor set.…”
Section: Model Designmentioning
confidence: 99%
“… Training is stopped when the cumulative increment in A U C o b t a i n e d i n f i v e consecutive steps is less than 1%. This rather soft stopping criterion is used instead of well-established statistical methods (Zhou et al, 2008) to avoid selecting too few predictors, which reduces the possibility of associating an effective probability of AHE with each integer score.  A testing dataset of the same size as the training set is used to evaluate model generalisation and to guide conclusive selection of the optimal predictor set.…”
Section: Model Designmentioning
confidence: 99%
“…We also calculate the variance of \documentclass{article}\usepackage{amsmath}\usepackage{amssymb}\usepackage{amsbsy}\usepackage{amsfonts}\pagestyle{empty}\begin{document}$\hat{\Delta}$ \end{document} from the explicit form derived by Wieand et al2 and Tang et al3 It is showed that for the large sample size, the Δ‐statistic \documentclass{article}\usepackage{amsmath}\usepackage{amssymb}\usepackage{amsbsy}\usepackage{amsfonts}\pagestyle{empty}\begin{document}$\hat\Delta=\hat\theta_1-\hat\theta_2$\end{document} is equivalent to the summation of i.i.d. random variables 5. If we define the B ‐value as \documentclass{article}\usepackage{amsmath}\usepackage{amssymb}\usepackage{amsbsy}\usepackage{amsfonts}\pagestyle{empty}\begin{document}$B(\tau_{i})=\hat{\Delta}\sqrt{\tau_{i}}/\sigma_{i}$ \end{document}, where τ i is the ratio of the Fisher information at the i th interim ( I i ) to the Fisher information at the K th look ( I K ) for \documentclass{article}\usepackage{amsmath}\usepackage{amssymb}\usepackage{amsbsy}\usepackage{amsfonts}\pagestyle{empty}\begin{document}$I_{i}=1/\sigma^{2}_{i}$ \end{document} and \documentclass{article}\usepackage{amsmath}\usepackage{amssymb}\usepackage{amsbsy}\usepackage{amsfonts}\pagestyle{empty}\begin{document}$I_{K}=1/\sigma^{2}_{K}$ \end{document}, respectively.…”
Section: Sequential Design In the Comparative Diagnostic Studymentioning
confidence: 99%
“…In addition, a nonparametric GSD model is proposed to compare the diagnostic accuracy of two markers 5. In their article, the following Delong's statistic is used to estimate the difference of two AUCs6: where The above two GSD methods are for comparing AUCs.…”
Section: Sequential Design In the Comparative Diagnostic Studymentioning
confidence: 99%
“…In diagnostic medicine, sequential testing procedures mainly focus on the discriminating accuracy of diagnostic tests. GSDs have been proposed to compare the receiver operating characteristics (ROC) curves and their areas using binormal distributions and empirical distributions ROC curves . More recently, researchers studied the GSD for predictive accuracy.…”
Section: Introductionmentioning
confidence: 99%